Pengaruh Komitmen Kerja, Fasilitas Kerja Dan Kepuasan Kerja Terhadap Kinerja Pegawai Terhadap Perusahaan Hanger Hasil Logam Kabupaten Tulungagung (Studi Kasus Pegawai Perusahaan Hanger Hasil Logam Kabupaten Tulungagung) - Amanah, Firnandya; Mardani, Ronny Malavia; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The types of problems that incorporate data studies involve the use of quantitative techniques. The research data linkage problem approach is presented in numerical form when the research data linkage problem is analyzed. In research that uses a combination of data search problems, there is a process that uses a combination of data search problems, data retrieval and identification of analytical tools. This type of research includes descriptive research, especially the problem of synthesizing research data, combining research data, exploratory research or photographing the problem of synthesizing research data, in-depth, broad and comprehensive research. Descriptive data matching problems include describing problems that combine data research on a specific population or domain with data aggregation research problems.. Keywords: work commitment, work facilities, job satisfaction, employee performance.